The economic and social performance of integrated photovoltaic and agricultural greenhouses systems: Case study in China. (15th March 2017) - Li, Changsheng; Wang, Haiyu; Miao, Hong; Ye, Bin
Highlights: Five basic integrated Photovoltaic greenhouses (PVGs) systems are introduced. Economic and social performance of five (PVGs) is assessed and analyzed. The impacts of key parameters on economic performance are investigated. Five PVGs' Annual Return on Investment (AROI) varies from about 9% to 20%. Abstract: Integrated photovoltaic (PV) and agricultural greenhouses (PVGs) have seen a rapid expansion in recent years in China. However, declining Feed-in Tariffs and underutilization of PV greenhouses also cause public concern regarding their actual economic performance. In this study, we address the economic and social performance of five PVGs based on a case study. The conclusions show that PVGs could achieve a good economic performance. Their Annual Return on Investment (AROI) varies from about 9% to 20% with a discounted payback period of 4–8 years depending on the different crops produced in PV greenhouses. Furthermore, PVGs also bring considerable social benefits, such as providing new jobs, raising taxes and avoiding substantial CO2 emissions. Sensitivity and uncertainty analysis reveals that crop price is the most sensitive influencing factor. The importance of the electricity feed-in tariff is much less than what we expected. This implies that PV agricultural companies should pay more attention to crop planting and that policy-makers should also shift the focus of incentives from PV power generation to agricultural crop production.